Cognitive tasks and combined statistical methods to evaluate, model, and predict mental workload - Louis, Lina-Estelle Linelle; Moussaoui, Saïd; Van Langhenhove, Aurélien; Ravoux, Sébastien; Le Jan, Thomas; Roualdes, Vincent; Milleville-Pennel, Isabelle (Frontiers in Psychology, 2023)
Mental workload (MWL) is a concept used as a reference for assessing the mental cost of activities. Nowadays, challenges related to user experience are determining the expected MWL value for a given activity and real-time adaptation of task complexity level to achieve or maintain desired MWL. As a consequence, it is important to have at least one task that can reliably predict the MWL level associated with a given complexity level. We used several cognitive tasks to meet this need, including the N-Back task, commonly used reference test in the MWL literature, and the Corsi test. Tasks were adapted to generate different MWL classes measured via NASA-TLX and Workload Profile questionnaires. Our first objective was to identify which tasks had the most distinct MWL classes based on combined statistical methods. Our results indicated that the Corsi test satisfied our first objective, obtaining three distinct MWL classes associated with three complexity levels offering therefore a reliable model (about 80% accuracy) to predicted MWL classes. Regarding our second objective to achieve or maintain the desired MWL, it entailed the use of an algorithm to adapt the MWL class based on an accurate prediction model. This model needed to be based on objective and real time indicator of MWL. For this purpose, we identified different performance criteria for each task. The classification models obtained indicated that only the Corsi test would be a good candidate for this aim (more than 50% accuracy compared to a chance level at 33%) but performances were not sufficient to consider identifying and adapting the MWL class online with sufficient accuracy during a task. Thus, performance indicators require to be complemented by other types of measures like physiological ones. Finally, we could highlight the limitations of the N-back task in favor of the Corsi test which turned out to be the best candidate to model and predict the MWL among several cognitive tasks.